The Digital Evolution of Taxation: Mapping Consultants' Perceptions of the Shift from Online Systematics to the Coretax System - Sastri, I I D A M Manik; Yoga, I Gst Agung Prama; Datrini, Luh Kade (Journal of Cultural Analysis and Social Change, 2025)
This study aims to analyze the influence of Perceived Ease of Use and System Reliability on the Perceived Usefulness of the Coretax system among tax consultants in Bali, Indonesia. Employing a quantitative research design, data was collected via an online questionnaire from a sample of 172 tax consultants, determined from a population of 300 using Slovin's formula. The data was analyzed using descriptive statistics and multiple linear regression to test the proposed hypotheses. The results indicate that both Perceived Ease of Use and System Reliability have a positive and statistically significant effect on Perceived Usefulness. Perceived Ease of Use was identified as the dominant factor influencing consultants' perception of the system's benefits. The regression model was found to be significant, explaining a substantial portion of the variance in Perceived Usefulness. The study's focus on tax consultants in Bali may limit the generalizability of the findings to other regions. Future research could incorporate additional variables and a broader geographical scope. For policymakers and the Directorate General of Taxes, these findings highlight the critical need to balance user-centric design with robust technical infrastructure. Enhancing the system's intuitiveness while ensuring its stability and reliability is paramount for increasing adoption and realizing the full benefits of the digital tax transformation. This study provides empirical evidence on the acceptance of a mandatory, profession-specific digital government system, extending the Technology Acceptance Model (TAM) by integrating the critical dimension of System Reliability within the context of a developing country's tax modernization.